Challenges in implementing the WHO-recommended package of care for advanced HIV disease in resource-constrained settings: A mixed-methods study - Temesgen Leka Lerango; Semalgn Leka Lerango; Mesfin Abebe; Tsion Mulat Tebeje; Habtamu Endashaw Hareru; Daniel Sisay; Getachew Assefa Zenebe; Yohannes Addisu; Biruk Bogale (PLoS ONE, 2026)
Background People diagnosed with advanced HIV disease (AHD) should be provided with the World Health Organization’s (WHO) package of care to address their specific healthcare needs. Although the WHO-recommended package of care is considered feasible and effective, its implementation remains sub-optimal across many sub-Saharan African (SSA) countries. This study aimed to explore challenges in implementing the WHO-recommended package of care for advanced HIV disease in resource-constrained settings. Methods A sequential explanatory mixed-methods study was conducted between March 1 and April 30, 2024, in the Gedeo Zone of Southern Ethiopia. The quantitative data involved extraction from medical records of 145 individuals newly diagnosed with AHD. For the qualitative inquiry, healthcare providers engaged in the HIV care continuum were purposively selected for in-depth key informant interviews. An inductive thematic analysis was conducted to identify and interpret recurrent patterns within the qualitative data. Quantitative data were analyzed using R version 4.3.3, while qualitative data were organized and managed using NVivo version 14. Results Only about half (47.6%) of the newly diagnosed AHD cases underwent baseline CD4 count testing. All 145 individuals were screened for TB using the WHO four-symptom algorithm, and 78.6% underwent confirmatory GeneXpert® MTB/RIF testing. Among individuals with AHD, 92.4% received co-trimoxazole prophylaxis, and 14.5% received tuberculosis preventive therapy. Rapid ART initiation was implemented for 20.0% of individuals with AHD. All newly diagnosed individuals with AHD received tailored counseling to ensure optimal adherence. Qualitative data analysis identified three principal challenges to the implementation of the WHO-recommended package of care: structural and organizational obstacles, service delivery constraints, and patient-related concerns as expressed by healthcare workers. Conclusions The implementation of the WHO-recommended package of care for individuals with AHD remains inconsistent. Although adherence support is routinely offered to all newly diagnosed individuals with AHD, the delivery of other key components is frequently hindered by a range of systemic challenges. These include the unavailability or frequent stockouts of essential medications and services for managing opportunistic infections, weak referral and linkage systems, and the absence of dedicated AHD care clinics. Such challenges underscore significant gaps in the continuum of AHD care and highlight the pressing need for targeted, system-level interventions to ensure comprehensive service delivery.